Session 2: Mutational discordance: the big challenge in personalized treatments – any solutions?. (May 2018) - Siddiqui, M.; Chand, M.; Eng, C.; Mehdizadeh, A.; Mirnezami, A.; Brown, G.
Abstract: The great challenge for oncologists treating patients who are developing or progressing with metastatic disease is to be able to offer a truly personalized and targeted therapy that can have an early and meaningful effect on the course of the disease. At present the known molecular markers are limited in their frequency and reliability in determining the use of newer chemotherapies. Professor Eng discusses the challenges faced in ensuring timely and effective treatments based on the molecular profile of the tumour and the potential role of real‐time analysis of mutational changes in the tumour when progression occurs.